The politics of problem solving: A co-evolutionary perspective on the recent scalar reorganisation of water governance in Germany - Andreas Thiel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
The European Union's Water Framework Directive advocates, among other things, River Basin Management and is often considered the principal driver of scalar organisation of gov-ernance in Europe. However, since more detailed comparative analysis seems necessary, this paper aims to enhance understanding of processes of scalar reorganisation of natural resource governance in the EU. A framework is developed for analysing the reconfiguration of water governance in Germany, relying on the illustrative case of the Elbe River basin. Drawing on a combination of theories of institutional change, the approach suggests a co-evolutionary understanding of processes concerning the scalar reorganisation of natural re-source governance, which turns out to be neither solely about politics or cost-effective gov-ernance. The framework enables highlighting of the diverse mechanisms of change in Ger-many, which led to a strengthening of the legislative function of the federal state and coordi-nation within basin boundaries, whereas individual states principally maintained an executive function. Upscaling was the outcome of European requirements, ideologically influencing changes in the preferences of water managers, facilitated by changes in use patterns. In-creasing contacts at multiple scales and in newly created fora led to an informal reorientation of water management in the Elbe basin while Germany-wide cooperation was sidelined. In comparison to other European countries, such as Spain or Portugal, where European re-quirements seem more politicized, Germany aspires to compliance with European require-ments in a functionalist fashion. Constitutional decision making rules seem to dominate which governance options are considered feasible and the extent of their potential stability.
Keywords: 330